2022
DOI: 10.3390/pr10020228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity on the Imbibition Recovery Process of Tight Sandstone Reservoirs

Abstract: Fracture network fracturing combined with oil–water infiltration and replacement is an effective approach to develop tight sandstone reservoirs. How to further improve oil recovery based on imbibition is a problem encountered during production. In this study, the core of the CHANG-7 tight sandstone reservoir in the Changqing oilfield of the China National Petroleum Corporation (CNPC) is studied. Combined with the newly designed core self-imbibition experiment, the mechanisms of salinity action are studied, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Surfactants primarily increase recovery by reducing surface tension and altering wettability, whereas imbibition agents enhance the fracturing fluid's penetration ability to achieve improved recovery. Integrated fracturing and recovery fluids utilize mechanisms such as interfacial adsorption, wettability alteration, micellar solubilization, and oil-water displacement to induce spontaneous imbibition and enhance crude oil recovery efficiency [19][20][21][22][23][24].…”
Section: Characteristics Of Integrated Fracturing and Enhanced Recove...mentioning
confidence: 99%
“…Surfactants primarily increase recovery by reducing surface tension and altering wettability, whereas imbibition agents enhance the fracturing fluid's penetration ability to achieve improved recovery. Integrated fracturing and recovery fluids utilize mechanisms such as interfacial adsorption, wettability alteration, micellar solubilization, and oil-water displacement to induce spontaneous imbibition and enhance crude oil recovery efficiency [19][20][21][22][23][24].…”
Section: Characteristics Of Integrated Fracturing and Enhanced Recove...mentioning
confidence: 99%
“…These tight reservoirs are predominantly developed via the huff-n-puff method, with enhanced oil production facilitated by spontaneous imbibition. , Consequently, the challenge of brine flooding in tight reservoirs is not a significant concern. The investigation by Liu et al observed that salinity exerts a significant influence on interfacial tension. In the presence of surfactants, the impact of brine salinity on interfacial tension may be negligible, while the salinity effect plays a crucial role in the imbibition process of tight oil reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…From the early stage of oilfield development to the middle and late stages with high water production, the recovery rate of tight sandstone reservoirs has decreased day by day. It has become a key task to make a strategy to enhance oil recovery by studying the controlling effect of pore permeability on residual oil (Li C. et al, 2022; [3,4].…”
Section: Introductionmentioning
confidence: 99%